Past Cigarette Smoking Is More Common among Those with Cholinergic Than Noncholinergic Dementias - Kyle Dalrymple; Erin K. Saito; Natalie Diaz; Julia Morrow; Beau Nakamoto; Aaron M. McMurtray (Neurology Research International)
Background. Patients with progressive dementing disorders associated with cortical cholinergic dysfunction gradually develop cholinergic deficits many years before symptom onset and may begin to smoke cigarettes during midlife as a form of self-medication. The aim of this study was to compare self-reported past smoking rates between those with and without cholinergic dementias, to determine if those who developed cholinergic dementias were more likely to smoke during midlife than those who did not. Methods. Retrospective cross-sectional study of past smoking status among patients treated at an outpatient clinic during a three-year period. Results. A total of 440 patients were evaluated during the study period, including 224 with cholinergic dementias and 216 with noncholinergic dementias and controls. Past smoking rates were greater among those with cholinergic dementias compared to those without cholinergic dementias (43.92% versus 26.96%, P=0.012). Additionally, smokers with cholinergic dementias reported significantly greater mean pack-years of smoking (P=0.038). Conclusions. Greater midlife smoking rates and greater pack-years of smoking were associated with cholinergic dementias. These results suggest midlife smoking may be an early indicator for those developing brain cholinergic deficits related to progressive dementing disorders and support initiating treatment prior to symptom onset in cholinergic dementias.